Implications of Error Analysis Studies for Academic Interventions. (February 2017) - Mather, Nancy; Wendling, Barbara J.
We reviewed 13 studies that focused on analyzing student errors on achievement tests from the Kaufman Test of Educational Achievement–Third edition (KTEA-3). The intent was to determine what instructional implications could be derived from in-depth error analysis. As we reviewed these studies, several themes emerged. We explain how a careful analysis of errors is key to planning the most appropriate instructional interventions.